Chapter Eight - Beyond “Victim Theology': Reconstructing Theological Education in an Era of HIV/AIDS in Africa - LeMarquand, Grant; Galgalo, Joseph D. (Theological Education in Contemporary Africa, 2013)
Part One addresses ëTheological Foundations.í The five essays in this section deal with the Bible, Theology and Ecumenism. The subjects of theological methods, contextual hermeneutics, and appropriate curriculum are given special attention. Of course even foundational issues cannot be discussed in a vacuum and so each of the essays addresses these foundational subjects in the light of African realities. Part Two deals with ëContemporary Issues.í It is particularly in this section that the traditional themes in African theology have been somewhat displaced by concerns which are today very pressing indeed. Three essays are devoted to the question of HIV/AIDS. This disease, which has devastated the African continent, demands a theological and practical response from those who claim to follow Jesus Christ. If the churches do not respond to this crisis with energy and determination we should not be surprised if the next generation wonders whether the Gospel has the power which we claim that it has. Two essays address the question of Islam and Muslim-Christian Relations in Africa. The resurgence of Islam in the world today is a concern of many. For those who believe in Jesus, this is a challenge which demands much wisdom and love. How should we respond to our Muslim neighbours? What are appropriate and thoughtful ways to share the love of Christ? Two further essays appear under the title of ëThe Marginalized.í This could, of course, be a much large section. Those who suffer from AIDS could be included in this number, and one might have expected to see at least one essay on the place of women. In this volume, however, the ëdisabledí and youth are highlighted. Both groups are clearly in need of the attention of the churches, and both groups are clearly misunderstood and neglected. The final section of Part Two contains essays, which focus attention on ëTheological Paedagogy.í All of the other contributions to this volume make suggestions and arguments about curriculum, resources, and issues of concern for theological educators. The causal aim of this book is that these essays may help us to reflect in an intentional way on the implications of contemporary realities for the future of theological education.